ANALISIS PENGARUH PERMODALAN, LIKUIDITAS DAN RENTABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA UNTUK PERIODE TH. 2007 - 2009 - Bardono, Heribertus Ari (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
The purpose of this study is to prove the effect of capital, liquidity and profitability are realized in the financial ratio Capital Adequacy Ratio (CAR), Return On Assets (ROA), Operating Expenses compared to Operating Income (BOPO) and Loan to Deposit Ratio (LDR), either partially or simultaneously to the Stock Return in the company banks listed on the Indonesia Stock Exchange (IDX) period 2007 â 2009. The study uses sample are 20 of Banking Companies listed on the Indonesia Stock Exchange (IDX) period 2007 â 2009. The results show that Capital Adequacy Ratio (CAR), Return On Assets (ROA), Operating Expenses compared to Operating Income (BOPO), and Loan to Deposit Ratio (LDR) jointly affect Stock Return. While partially the results show that only the Return On Assets (ROA) and Operating Expenses compared to Operating Income (BOPO) that affect Stock Return.